Molecular Mechanisms of Synaptic Dysregulation in Fragile X Syndrome and Autism Spectrum Disorders - Telias, Michael (Frontiers in Molecular Neuroscience, 2019)
Fragile X syndrome (FXS) is the most common form of monogenic hereditary cognitive impairment. FXS patient exhibit a high comorbidity rate with autism spectrum disorders (ASDs). This makes FXS a model disease for understanding how synaptic dysregulation alters neuronal excitability, learning and memory, social behavior, and more. Since 1991, with the discovery of FMR1 as the sole gene that is mutated in FXS, thousands of studies into the function of the gene and its encoded protein FMRP, have been conducted, yielding important information regarding the pathophysiology of the disease, as well as insight into basic synaptic mechanisms that control neuronal networking and circuitry. Among the most important, are molecular mechanisms directly involved in plasticity, including glutamate and GABA receptors, which can control synaptic transmission and signal transduction, including short- and long-term plastic neuronal events. More recently, several novel mechanisms involving growth factors, enzymatic cascades and transcription factors, have been proposed to have the potential of explaining some of the synaptic dysregulation in FXS. In this review, I summarize and criticize the main mechanisms proposed to underlie synaptic disruption in FXS and ASDs. I focused on studies conducted on the Fmr1 knock-out mouse model and on FXS-human pluripotent stem cells, emphasizing the differences and even contradictions between mouse and human, whenever possible. As FXS and ASDs are both neurodevelopmental disorders that follow a specific time-course of disease progression, I highlight those studies focusing on the differential developmental regulation of synaptic abnormalities in these diseases.